Midwifery Care for Pregnant Women Ny.E G1p0a0 With Placenta Previa at Al-Firah Maternity Clinic Tanjung Pura Using Midwifery Management Approach According to Varney in 2019 - Setia Sihombing; Miranti; Siti Sundari (Science Midwifery, 2019)
Based on the results of the 2015 Inter-Census Population Survey (SUPAS), the MMR in Indonesia again showed a decline to 305/100,000 live births. The causes of maternal death in Indonesia include placenta previa, namely 2.77% in 2015 and 0.85% of them died. Type of case study report with descriptive method, location at Al-Fitrah Maternity Clinic Tanjung Pura. Data collection techniques include primary data including physical examination, interviews and observation and secondary data, including documentation studies and literature studies. Able to carry out midwifery care for pregnant women with placenta previa using Varney's 7-step midwifery approach. For midwifery care for pregnant women at the Al-Fitrah Maternity Clinic Tanjung Pura, after carrying out midwifery care for 3 days, the results were: Bleeding stopped, there are no contractions and the general condition of the mother and fetus is good. There is no gap between theory and practice so a potential diagnosis of hypopolemic shock does not occur. The results of midwifery care carried out for 3 days the mother came home in good condition and there was no bleeding.